(3GdOQ GdfKjQ aj JdNjU fgGjI GHf GdGKjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe gPG eDda dNUJ ajg cJGH GdfgGjI ai ZQjH GdMOjK dGHf GdCKjQ , SejJg HGdOQ GdfKjQ , HMjK de CZGOQ efg TjFkG hdG GdfRQ GdjSjQ , hVeeJ Edjg s
(3BNQgG (B:s
(3HjYJ UbY Je GdcJGH , hbGd eDdag (B: (3aQZfG ef JGdjag jhe YjO GdaWQ SfI SHY hJSYeGFI hddg GdMeO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B359s
(3HgG fXGe GdJYbjHIs
(3cJHJ CdaGX GdZQjH HGdMeQIs
(3YdjgG Jedc HGSe eMeO Hf CMeO Hf Jbi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs